2017
DOI: 10.1007/s11739-017-1696-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lercanidipine plus hydrochlorothiazide vs. lercanidipine plus enalapril on micro and macrocirculation in patients with mild essential hypertension

Abstract: Dihydropyridine calcium channel blockers may possess antioxidant properties, and might improve micro and macrovascular structure and function. Combination treatment with an ACE inhibitor may have additional advantages, compared with a thiazide diuretic. The aim of the present study is to investigate the effects of a short-term treatment with lercanidipine, and to compare two combination treatments: lercanidipine + enalapril vs. lercanidipine + hydrochlorothiazide on structural alterations in retinal arterioles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
0
6
0
1
Order By: Relevance
“…Gallo and coworkers 74 found no significant difference between the effects of different classes of antihypertensive treatment on retinal microvascular remodeling, whereas a multivariate analysis by Rosenbaum and coworkers 73 showed that hypertension drug regimen was not an independent predictor of any retinal anatomical indices. In contrast, De Ciuceis and coworkers 79 found a significant reduction in the wall-to-lumen ratio of hypertensive patients after undergoing combined lercanidipine and enalapril treatments over a period of 24 weeks.…”
Section: Adaptive Optics Imagingmentioning
confidence: 83%
See 1 more Smart Citation
“…Gallo and coworkers 74 found no significant difference between the effects of different classes of antihypertensive treatment on retinal microvascular remodeling, whereas a multivariate analysis by Rosenbaum and coworkers 73 showed that hypertension drug regimen was not an independent predictor of any retinal anatomical indices. In contrast, De Ciuceis and coworkers 79 found a significant reduction in the wall-to-lumen ratio of hypertensive patients after undergoing combined lercanidipine and enalapril treatments over a period of 24 weeks.…”
Section: Adaptive Optics Imagingmentioning
confidence: 83%
“…This is because it is tedious to capture AO images and can be exhausting for patients. Furthermore, as the region of analysis in AO imaging is often limited to a single vessel in a limited field of view, usually a segment of the superotemporal arterioles, 3,68,[73][74][75]79 it is difficult to be certain that the changes in that arteriole are reflective of all other retinal vessels. In the future, large field-of-view montages may be attractive and will potentially yield more reliable information on the microcirculatory status.…”
Section: Limitations Of Adaptive Optics Imagingmentioning
confidence: 99%
“…Ciuceis and coworkers 14 found a significant difference in WLR in hypertensive patients when lercanidipine and enalapril treatments were combined over a period of 24 weeks,…”
Section: Wall-to-lumen Ratiomentioning
confidence: 98%
“…Помимо «двойного» вазодилатирующего эффекта (блокирование прямого вазоконстрикторного действия ангиотензина II и активности симпатической нервной системы), ингибиторы АПФ уменьшают потребность миокарда в кислороде и ингибируют высвобождение альдостерона, тем самым снижая внутрисосудистый объем и преднагрузку. С другой стороны, амлодипин, как блокатор медленных кальциевых каналов, являясь мощным вазодилататором артериолярного русла и коронарных артерий, также обладает антиоксидантным действием [13]. За счет ингибирования трансмембранного перехода ионов кальция внутрь гладкомышечных клеток сердца и сосудов амлодипин расширяет периферические артериолы и снижает ОПС (постнагрузку).…”
Section: Discussionunclassified